Delayed plastic responses to anodal tDCS in older adults - Fujiyama, Hakuei; Hyde, Jane; Hinder, Mark R.; Kim, Seok-Jin; McCormack, Graeme H.; Vickers, James C.; Summers, Jeffery J. (Frontiers in Aging Neuroscience, 2014)
Despite the abundance of research reporting the neurophysiological and behavioral effects of transcranial direct current stimulation (tDCS) in healthy young adults and clinical populations, the extent of potential neuroplastic changes induced by tDCS in healthy older adults is not well understood. The present study compared the extent and time course of anodal tDCS-induced plastic changes in primary motor cortex (M1) in young and older adults. Furthermore, as it has been suggested that neuroplasiticity and associated learning depends on the brain-derived neurotrophic factor (BDNF) gene polymorphisms, we also assessed the impact of BDNF polymorphism on these effects. Corticospinal excitability was examined using transcranial magnetic stimulation before and following (0, 10, 20, 30 min) anodal tDCS (30 min, 1 mA) or sham in young and older adults. While the overall extent of increases in corticospinal excitability induced by anodal tDCS did not vary reliably between young and older adults, older adults exhibited a delayed response; the largest increase in corticospinal excitability occurred 30 min following stimulation for older adults, but immediately post-stimulation for the young group. BDNF genotype did not result in significant differences in the observed excitability increases for either age group. The present study suggests that tDCS-induced plastic changes are delayed as a result of healthy aging, but that the overall efficacy of the plasticity mechanism remains unaffected.